Morning English Program (MEP) as a Strategy to Improve Students' Speaking Skills at SMK Bhakti Mulia Pare Kediri - Anshori, Mohammad Isya; Shofiya, Arina; Iftanti, Erna (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This study aims to describe the activities of MEP and their impact on improving students' speaking skills. This study applied a descriptive quantitative method. In collecting the data, the researchers of the administered questionnaire were divided into two groups: an English teacher at SMK Bhakti Mulia Pare and 11th-grade students who became members of the MEP. Then, the researcher interviewed five students and one teacher to expand the information received. Data analysis was done by calculating the percentage of students' participation in each activity. The supporting qualitative data was analyzed by collecting, displaying, and drawing conclusions. The reliability of the study data was checked through data triangulation. The results of this study showed that the MEP activities consisted of speeches, reading aloud, telling stories and group discussions. Following the implementation of these activities, students' speaking skills, which include grammatical accuracy, pronunciation skills, vocabulary mastery, fluidity, and the ability to organize concepts in speaking, improve. In addition, students experience low anxiety and are more interested in learning English. This positive impact results from the teacher's role in preparing appropriate teaching methods and creating a positive learning environment. Henceforth, this study emphasizes the importance of planning before implementing an English program and adopting similar activities to improve students' speaking skills.